In Vitro Inhibition of Calcium Oxalate Crystallization by Phagnalon rupestre aqueous extract (Journal of Medical Sciences, 2023)
Kidney stone disease is a common urologic condition that affects around 10% of the general population at some point in their lives. Unfortunately, currently, available management aims to treat the result of an underlying metabolic abnormality, which results in further recurrence. The formation of urinary stones is related to decreased urine volume or increased excretion of stone-forming components. With its multifactor etiology and high rate of recurrences, kidney stone provides a medical challenge; therefore, there is a demanding need to prevent this disease and its recurrence. In Libya, using herbal medicines, especially Phagnalon rupestre, as a traditional therapy to treat kidney stones is not science-based, though it is widely used. Therefore, this study aims to evaluate the effect of Phagnalon rupestre extract on the dissolution of calcium oxalate stones. The aqueous plant extract was extracted from the dried aerial parts of Phagnalon rupestre using the reflux method. Using spectrophotometric methods, the nucleation of calcium oxalate crystals was measured. The inhibitory effect of herb extract on the nucleation growth of calcium oxalate formation was compared with that of the control.Interestingly, the highest dissolution rate of calcium oxalate crystals was observed by the Phagnalon rupestre extract in comparison to the control. Our results demonstrate that an extract of Phagnalon rupestre inhibits the nucleation of calcium oxalate crystals. The extract of Phagnalon rupestre may contain substances that inhibit calcium oxalate crystal aggregation. Future work will focus on testing the extract in vivo and confirming our findings in an animal model.